ASSESSMENT OF NUTRITIONAL STATUS TO DETERMINE THE PREVALENCE OF MALNUTRITION IN PATIENTS UNDERGOING SURGERY FOR COLORECTAL CARCINOMA USING INA SCORE - MUQEET, A; HAIDER, S; IBRAHIM, F; HYDER, A; SIRAJ , MI; SAJID, EU; RAJPUT, IA; KHAN, NA (Biological and Clinical Sciences Research Journal, 2024)
Colorectal cancer (CRC) is the third most commonly diagnosed malignancy worldwide. Malnutrition is a critical factor influencing postoperative morbidity and mortality in CRC patients. Surgical trauma exacerbates the metabolic response, increasing the risk of malnutrition-related complications such as cancer cachexia and reduced efficacy of postoperative chemotherapy or radiotherapy. This study aimed to assess the prevalence of malnutrition in patients undergoing surgery for colorectal carcinoma using the Instant Nutritional Assessment (INA) score. Objective: To determine the frequency and degree of malnutrition in patients undergoing resection surgery for colorectal carcinoma using the INA score. Methods: This cross-sectional study was conducted in the Department of Surgery at Dr. Ruth K. M. Pfau Civil Hospital Karachi over six months, from October 1, 2022, to March 31, 2023. A total of 93 patients undergoing elective resection for colorectal carcinoma were enrolled. Demographic and clinical data, including histological diagnoses, were recorded using a predesigned proforma. Nutritional status was assessed using the INA score, based on serum albumin levels and blood lymphocyte counts. Malnutrition was classified into four degrees according to operational definitions. Data analysis was performed using SPSS version 19. Results: The mean age of participants was 47.60 ± 12.87 years. Of the 93 patients, 56.99% were male, and 43.01% were female. The frequency of malnutrition was 27.96% (26/93), with malnutrition degrees distributed as follows: 8 patients (30.8%) with first-degree, 5 patients (19.23%) with second-degree, 9 patients (34.62%) with third-degree, and 4 patients (15.38%) with fourth-degree malnutrition. Conclusion: A significant proportion of patients undergoing surgery for colorectal carcinoma were found to be malnourished. These findings underscore the necessity for routine preoperative nutritional assessments and timely interventions to improve surgical outcomes and enhance the effectiveness of postoperative therapies. Incorporating nutritional support as a standard component of colorectal cancer care can mitigate the risk of cancer cachexia and associated complications.